2011
DOI: 10.1111/j.1365-2915.2011.00993.x
|View full text |Cite
|
Sign up to set email alerts
|

Larval nutritional stress affects vector immune traits in adult yellow fever mosquito Aedes aegypti (Stegomyia aegypti)

Abstract: We report key physiological traits that link larval nutritional experience to adult immune status in the yellow fever mosquito Aedes aegypti L. (Stegomyia aegypti) (Diptera: Culicidae). Many lines of defence make up the innate immune system of mosquitoes. Among defences, the epithelium-lined midgut is the first barrier, circulating haemocytes are cellular components of innate immunity and, when triggered, the Toll and Imd pathways signal production of antimicrobial peptides (AMP) as part of humoral defences. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
70
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 60 publications
10
70
0
1
Order By: Relevance
“…Along the same lines, nutrient-deprivation during the larval stages enhanced infection and transmission (horizontal and vertical) of LaCrosse encephalitits virus by Aedes triseriatus (Say; Grimstad and Haramis 1984, Patrican and DeFoliart 1985, Grimstad and Walker 1991. Together these observations are consistent with observations that temperature and nutrition may alter the expression of immunity-related genes and viral competence (Telang et al 2012, Muturi et al 2011c. Specifically, cooler rearing conditions may compromise the immune system in Ae.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Along the same lines, nutrient-deprivation during the larval stages enhanced infection and transmission (horizontal and vertical) of LaCrosse encephalitits virus by Aedes triseriatus (Say; Grimstad and Haramis 1984, Patrican and DeFoliart 1985, Grimstad and Walker 1991. Together these observations are consistent with observations that temperature and nutrition may alter the expression of immunity-related genes and viral competence (Telang et al 2012, Muturi et al 2011c. Specifically, cooler rearing conditions may compromise the immune system in Ae.…”
Section: Discussionsupporting
confidence: 77%
“…albopictus larvae primarily inhabit water-filled artificial containers like water storage containers, plant vases, and tires. Container habitats often are associated with episodic and irregular inputs of basal nutrients and crowded larval conditions causing larvae to experience food limitation (Southwood et al 1972, Subra and Mouchet 1984, Arrivillaga and Barrera 2004, Juliano 2007, Padmanabha et al 2010, which may affect adult nutrient reserves (Briegel 1990) and so may influence adult morphology (size) and physiology (immune functions; Ahmed et al 2002, Schwartz and Koella 2004, Telang et al 2012, Kim and Muturi et al 2013. Temperature in these container habitats may also affect mosquito larval development and survival within food-limited conditions by modifying feeding rate, efficiency of food conversion into biomass, or ability to survive starvation (Rashed andMulla 1989, Padmanabha et al 2011).…”
mentioning
confidence: 99%
“…competition, predation and food shortage) experienced during vector larval development can have a profound impact on life-history traits (e.g. growth rate, fecundity and longevity) [16][17][18][19] and thus potentially impact pathogen transmission through changes in adult vectorial capacity. For example, recent studies have shown that intra-and interspecific competition during mosquito larval development can weigh heavily on the transmission of filarial worms and arboviruses through indirect carryover effects on vector -pathogen interactions [20 -22].…”
Section: Introductionmentioning
confidence: 99%
“…Limited resource availability for larvae or adults can result in reduced larval survivorship and adult life span (Costanzo et al 2005, Reiskind and Lounibos 2009, Gilles et al 2011, Alto et al 2012, lower fecundity (e.g., Mostowy and Foster 2004, Vaidyanathan et al 2008, Xue et al 2010, and altered immune function (Suwanchaichinda and Paskewitz 1998, Koella and Sorenson 2002, Telang et al 2012, Ponton et al 2013. Resource availability for larvae or adults can affect vector competence for viruses, Plasmodium, and filarial parasites (Okech et al 2004(Okech et al , 2007Vaidyanathan et al 2008;Alto and Lounibos 2013;Breaux et al 2014).…”
mentioning
confidence: 99%